The Result of Divorce on the Gono Gini Assets Decision on Case No: 1451/Pdt.G/2016/PA Kdl - Muchamad Satria Lesmana (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Humans by nature are zoon politicon, which are social creatures. This means that humans are destined to live in society and interact with each other. Humans cannot live alone without help from others, because they always seek and need other humans to live together and then organize socially. In this case the smallest form of human life together begins with the existence or by forming a family. All Indonesian people have the same legal guidelines that regulate marriage issues, namely Act No. 1 of 1974 concerning Marriage. Which is also equipped with implementing regulations, namely Government Regulation Number 9 of 1975. The sound of Act No. 1 of 1974, in Article 1 has explained that what is meant by